Philosophy and the Physics of the Damned, By Cormac McCarthy, Patrick O’Connor - Baillie, Eva (Literature and theology, 2025)
Patrick O’Connor’s latest book is an exploration of Cormac McCarthy’s writings in relation to his philosophical perspectives. O’Connor is a Senior Lecturer